2016
DOI: 10.7314/apjcp.2016.17.3.1261
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p53 Breast Cancer in Kurdish Women in the West of Iran: a Reverse Correlation with Lymph Node Metastasis

Abstract: Background: In breast cancer (BC), it has been suggested that nuclear overexpression of p53 protein might be an indicator of poor prognosis. The aim of the current study was to evaluate the expression of p53 BC in Kurdish women from the West of Iran and its correlation with other clinicopathology figures. Materials and Methods: In the present retrospective study, 231 patients were investigated for estrogen receptor (ER) and progesterone receptor (PR) positivity, defined as ≥10% positive tumor cells with nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
7
5
0
Order By: Relevance
“…Thus p53 expression was seen in 41.66% of the cases. This is comparable with the work of Madani et al, 12 Wang XZ et al, 10 Payandeh et al 13 and Kikuchi et al 11 There is a wide variation in the expression of p53 amongst different authors. These differences may be due to heterogenous group of population, different methods for assaying p53, or different cut offs to designate high or low p53 expression.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus p53 expression was seen in 41.66% of the cases. This is comparable with the work of Madani et al, 12 Wang XZ et al, 10 Payandeh et al 13 and Kikuchi et al 11 There is a wide variation in the expression of p53 amongst different authors. These differences may be due to heterogenous group of population, different methods for assaying p53, or different cut offs to designate high or low p53 expression.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, 56.67% of the breast cancers were highly proliferative while 43.33% cases had low Ki 67 proliferative index which is similar to the studies done by Madani SH et al, 12 Wang XZ et al, 10 Payandeh et al 13 and Hassan I et al 14 Also the mean Ki LI was found to be 28 (±20.27) with a range of 2-80%. According to various literatures, the cut off for Ki-67 LI has varied from 5 to 30%.…”
Section: Discussionsupporting
confidence: 89%
“…It was shown that the TP53 16-bp INS/DEL polymorphism can be associated with risk of BC among a sub population of Iranian patients [54]. There was also significant correlations between p53 expression, lymph node involvement, age, and tumor grade in Kurdish BC patients in Western Iran [55]. The mitochondrial pathway of apoptosis process is associated with BCL-2 which is also a prognostic factor in BC for its relation with defence mechanisms against the genotoxic damages [56, 57].…”
Section: Main Textmentioning
confidence: 99%
“…Breast cancer (BC) is a heterogeneous disorder with different pathological and histological characteristics [1]. Based on the latest statistics from the International Agency for Research on Cancer (IARC), 1,677,000 women were diagnosed with BC in 2012 and 577,000 died [2].…”
Section: Introductionmentioning
confidence: 99%
“…BC can be classified into different subtypes based on the diagnosis of oestrogen receptor (OR), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2) [1]. Recurrence risk in BC changes during the follow-up time [6].…”
Section: Introductionmentioning
confidence: 99%